Comparison of Borderline and Schizotypal Personality and Their Components in Ethnic Groups - احمد ولیخانی; مهدی ایمانی (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2016)
Aim and Background : In recent decades, culture and personality have been the focus of many psychologists and anthropologists around the world. Many studies have been conducted regarding this topic in the West; however, despite the various cultures and ethnicities in Iran, this subject has been overlooked by Iranian researchers. Thus, the present study aims to draw a comparison between borderline and schizotypal personality traits and their components among Fars, Turk, Kurd, and Lur students. Methods and Materials : This causal-comparative study was conducted on 200 students of Shiraz University of Medical Sciences, Iran. The participants were selected through convenience sampling and completed the Borderline Personality (STB) and Schizotypal Personality (STA) Questionnaires. Data were analyzed using MANOVA.   Findings : No significant difference was observed between the ethnic groups in terms of borderline and schizotypal personality traits (P < 0.05). Among the components of schizotypal and borderline personality traits, respectively, magical thinking and disappointment differed significantly among the ethnic groups (P < 0.01). In terms of magical thinking, Kurd and Turk students, compared to Fars and Lur students, gained higher scores. . In addition, in terms of the component of disappointment, there was only a significant difference between Kurd and Turk students; Kurd students obtained higher scores in comparison to Turk students. Conclusions : Based on these results, it can be concluded that ethnicity can affect personality. However, further studies are required in this area across Iranian ethnic groups.